ERA OF SUSTAINABILITY: DO THE ECONOMIC, SOCIAL, AND ENVIRONMENTAL ASPECTS HAVE A POSITIVE IMPACT ON COMMUNITY-BASED ECOTOURISM? - Septiani, Delina Herdian; Rahmani, Hani Fitria; Sriwijayanti, Irma; Pratiwi, Ratih (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
Indonesia's tourism industry is undergoing a shift toward nature-based and sustainable tourism, creating opportunities for the development of community-based ecotourism. This study aims to analyze the economic, social, and environmental impacts of ecotourism development in AEWO Mulyaharja, Bogor City. A quantitative descriptive approach was used, with purposive sampling involving local communities, tourism managers, business owners, tourists, and government representatives. Data were collected through questionnaires and structured interviews and analyzed using statistical tests in SPSS. The results indicate that stakeholder perceptions of the ecotourism impact fall into the